Properties of Pineapple Leaf Fibers with Paper Waste as An Absorbing-Composite to Reduce Noise - Sari, Kartika; Isnen, Yazid Zainur; Utomo, Agung Bambang Setio; Sunardi, Sunardi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2022)
Natural product-based noise-absorbing composite can be an alternative to replace synthetic fiber because of its advantages of high strength, toughness, low price, and abundance to reduce noise. The materials used were pineapple leaf fibers with paper waste. This research aims to study the advantage of natural products to reduce noise by analyzing the coefficient of sound absorption and impact strength to evaluate the absorbing composite. The composites were tested with the Charpy method with ISO 11654 standard and ASTM E23 for sound absorption and impact strength. Sound absorption was carried out using an impedance tube at a frequency range of 250 – 3000 Hz. The volume fraction of pineapple leaf fibers, paper waste, and resin epoxy concentrations were 20% : 30% : 50%, 25% : 25% : 50%, and 30% : 20% : 50%. The thickness for the sound absorption coefficient was 2 cm and 3 cm, while the thickness of the impact strength was 0.5 cm. The highest sound absorption coefficient of pineapple leaf fibers composite for 30% : 20% : 50% volume fraction was 0.788 for sample 2 cm. The highest impact strength for 20% : 30% : 50% volume fraction of the thickness of 0.5 cm was 3.527 J/mm2. The results of the sound absorption coefficient will increase if used more pineapple leaf fibers but it will decrease the impact strength. Based on this research, the pineapple leaf fibers will improve the quality of the composite that can be used as a sound-absorbing material as well. These materials possess the promising potential to decrease waste and are used in industries for a low cost.